Effects of resistance training in women with fibromyalgia: An integrative review (Research, Society and Development, 2023)
Fibromyalgia (FM) is characterized as a rheumatological, serious debilitating disease, and the main symptoms are chronic and diffuse musculoskeletal pain, tiredness, fatigue, sleep disturbance and, in some cases, joint stiffness. Fibromyalgia is a chronic pain condition that mostly affects women. Objectives: This review is to analyze studies that examined the impact of resistance training on the health of women with fibromyalgia. Methods: "This is a qualitative integrative review of the literature, directed from the following question: "Is resistance training effective in the treatment of fibromyalgia?". The search for articles was carried out in the databases: Lilacs, MEDLINE/ PubMed, in the months of January and February 2023. 168 articles were identified. After applying the inclusion and exclusion criteria, 30 articles were selected that were relevant. But after a detailed analysis, 9 articles were selected. A reading and critical analysis of all articles included.Results: Overall, the results of these studies suggest that resistance training is a viable and consistent strategy for the effective treatment of fibromyalgia.